2016
DOI: 10.1007/s12094-016-1569-y
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of OCT4 may sensitize NSCLC cells to cisplatin

Abstract: Our findings indicate that targeting OCT4 could improve cisplatin effect in NSCLC, confirming their role in modulating cisplatin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Maybe Cisplatin (8 μg/ml) still could affect other pro-apoptosis genes that could induce cell apoptosis. Similarly, Liu et al’s [44] research also supported ours. And a more in-depth research will be launched in the future study to explain this result clearly.…”
Section: Discussionsupporting
confidence: 88%
“…Maybe Cisplatin (8 μg/ml) still could affect other pro-apoptosis genes that could induce cell apoptosis. Similarly, Liu et al’s [44] research also supported ours. And a more in-depth research will be launched in the future study to explain this result clearly.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, Oct4 downregulation has been strongly associated with cancer invasion suppression [4749] and chemosensitization [50] in different neoplasms, which indicates that Oct4 could be useful as a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated OCT4 expression has been reported in many tumor types including NSCLC, and the expression levels of OCT4 mRNA and protein were significantly higher in tumor tissues compared with adjacent normal tissues [7]. Researchers revealed that OCT4 is linked to chemoresistance to cisplatin in NSCLC cells, suggesting that OCT4 inhibition may be a potential strategy for chemosensitization of NSCLC cells [8]. Clinical studies further validated the importance of the OCT4/NEAT1/MALAT1 signaling axis in lung cancer progression [9].…”
Section: Introductionmentioning
confidence: 97%